ON CERTAIN SUB-SPACE OF X (Baghdad Science Journal, 2008)
The study of properties of space of entire functions of several complex variables was initiated by Kamthan [4] using the topological properties of the space. We have introduced in this paper the sub-space of space of entire functions of several complex variables which is studied by Kamthan.